The Fatigue Assessment Scale: quality and availability in sarcoidosis and other diseases. Issue 5 (September 2018) - Hendriks, Celine; Drent, Marjolein; Elfferich, Marjon; De Vries, Jolanda
Abstract : Purpose of review: Fatigue is a problem experienced by many patients suffering from chronic diseases, including sarcoidosis patients. It has a substantial influence on patients' quality of life (QoL). It is, therefore, important to properly assess fatigue with a valid and reliable measure. The Fatigue Assessment Scale (FAS) is the only validated self-reporting instrument classifying fatigue in sarcoidosis. The aim of this review was to examine the psychometric properties of the FAS and the diseases and languages in which it has been used. Studies among sarcoidosis patients were also reviewed in terms of outcomes. Recent findings: Studies were identified by searching the electronic bibliographic database Pubmed. Search terms used were: FAS and fatigue. Articles were included in the review if the FAS had been used to assess fatigue. Results: Since its introduction, the FAS was used in 26 different diseases or conditions, including stroke, neurologic disorders, rheumatoid arthritis, idiopathic pulmonary fibrosis and sarcoidosis. Its reliability and validity have proved to be good. Unidimensionality has been established. So far, the FAS is available in 20 languages and widely used in sarcoidosis. Digital versions as well as PDFs of various languages are available online (www.wasog.org ). Summary: The FAS has good psychometric qualities for the diseases in which it has been examined, including sarcoidosis, and can be used in clinical practice. Healthcare workers can use the FAS to assess fatigue in the management, follow-up and clinical care programmes for their patients consistently across countries, as well as in clinical research.